Toxigenic Capacity and Trichothecene Production by Fusarium graminearum Isolates from Argentina and Their Relationship with Aggressiveness and Fungal Expansion in the Wheat Spike - Malbrán, Ismael (2014)
At least 20 epidemics of Fusarium head blight (FHB) of wheat have been registered in the last 50 years in Argentina, with variable intensity. Damage induced by the disease is further aggravated by the presence of mycotoxins in affected grains that may cause health problems to humans and animals. The trichothecene chemotype was analyzed for 112 isolates of Fusarium graminearum from Argentina by polymerase chain reaction and two field trials were conducted to study the aggressiveness of a subsample of 14 representative isolates and to analyze deoxynivalenol (DON) production in planta and in vitro. All isolates belonged to the 15- acetyl-DON chemotype. Significant differences were observed in both the symptom severity induced in wheat spikes and the in vivo DON production, and a close correlation was found between these two variables. However, in vitro toxigenic potential was not correlated with the capacity of F. graminearum isolates to produce DON under natural conditions. The progress of infection in the rachis of inoculated wheat spikes was analyzed and the pathogen presence verified in both symptomatic and symptomless spikes. Even isolates with a limited capacity to induce symptoms were able to colonize the vascular tissue and to produce considerable amounts of DON in planta.